A refundação da nação e o conceito de bolivarianismo nos discursos de Hugo Chávez Frías de 1999-2000 - ZANCOPE, Tiago Ciro Moral (2012)
The objective of this thesis is to analyze the rise of Hugo Chávez Frías to the presidency of Venezuela in 1999. His first speeches highlighted the need to refound the nation, under new parameters, created from his interpretation of the acts of Bolívar, therefore, his main proposal would be the creation of the República Bolivariana de Venezuela, which, distinctly from the previous ones, should symbolize the union of the nation with the ideas of its beloved son: Simón Bolívar. In order that operation could reach the intended success, it was necessary modify its sustenance pillars. These alterations were accomplished through the redaction of a new constitution, by the redistribution of the powers and also via the historic narrative, which instead of support itself in the historiography, was proclaimed bolivariana. Thus, the V República, that emerges was displayed as the unrolling of the independence war period in the XIX century. The association between the new Republic and the most glorious moment of the country s history, not only legitimated, but is also equivalent to the projection of the values and the brilliancy of formerly. Accordingly, sought to comprehend this phenomenon under one synchronic view, in other words, examining his specificities in order to identify possible points of changes and permanency, because, concomitantly, observing his diachronic, that is, the way how this strategy evolved over the time, in view of the fact that the president s of Venezuela repeatedly asseverate to act over the principals of the bolivarian philosophy. From then on, was reflected about the national paradox, in which the orientation in present seen as meaningless motivated the constant return to the past nineteenth century, since there would be a source of solutions for any kind of demand. The República Bolivariana de Venezuela is, in this sense, the radicalization of this aporia as well as the cult of Bolívar in the attempt to orient the nation and society on a premise which mobilize them in the direction of one bolivarian future and, which below the auspicious of the present, would complement one circle of the conflicts eradication.